PEMANFAATAN SUMBER DAYA ALAM DALAM BIDANG PARIWISATA - Sandy Sulistiono; Widyawati Boediningsih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Indonesia's natural resources are famous for their beauty abroad. With its amazing naturalbeauty, it opens up opportunities for people and countries to take advantage of it by organizing tourism onthese natural resources. However, the act of utilizing natural resources cannot be carried out haphazardly,but is based on the state constitution, namely the 1945 Constitution of the Republic of Indonesia.Therefore, this research will examine the direction of regulation and policy on the use of natural resourcesin national law. as well as the use of natural resources in the tourism sector based on the 1945Constitution of the Republic of Indonesia. Because this research is legal research, the approach used is aconceptual approach related to the legal concept of natural resources which is applied supported by alegislative approach related to provisions. tourism law provisionsjuxtaposed with the 1945 Constitution ofthe Republic of Indonesia.